Knowledge-oriented management systems for complex objects - Palagin, O.; Symonov, D. (Проблеми керування та інформатики, 2024)
The article examines the issue of improving the efficiency of complex systems management through the use of knowledge-based methods and technologies. The article emphasizes the need to revise traditional approaches to scientific research and knowledge management by introducing a transdisciplinary paradigm and artificial intelligence to achieve sustainable development and knowledge evolution. Розглядається питання підвищення ефективності керування складними системами з використанням методів і технологій, заснованих на знаннях. Наголошується на необхідності перегляду традиційних підходів до наукових досліджень та керування знаннями через впровадження трансдисциплінарної парадигми та штучного інтелекту для досягнення сталого розвитку та еволюції знань.